In Vitro Susceptibilty Test of Fluconazole to Candida spp in Patients with Oropharyngeal Candidiasis and HIV/AIDS with Vitek II - Novianti Rizky Reza; Tantari SHW; Santosa Basuki (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2017)
Background: Oral candidiasis (OC) was the most common opportunistic infection in HIV/AIDS. Widespread and inadequate use of fluconazole as a prophylaxis and therapy in OC resulted in decreasing susceptibility. Decreased susceptibility of fluconazole will show the increasing in vitro Minimum Inhibitory Concentration (MIC) was reported in some studies. Purpose: To determine in vitro susceptibilty of fluconazole to Candida spp in patients with Oropharyngeal Candidiasis and HIV/AIDS. Methods: The study design was descriptive, observational, cross sectional study for three months in Saiful Anwar Hospital Malang. Species identification and fluconazole susceptibility used Vitek II. Result: Thirty three subject with 36 Candida isolates. Candida albicans was the most common species identified in 86% isolates,  C. krusei  8%, and C. glabrata 6%.  C. albicans had MIC between ≤ 1 mg/l – 16 mg/l, C. glabrata 4mg/l, dan C. krusei 2 mg/l - 32 mg/l. Sensitivity of C. albicans to fluconazole was demonstrated in 83% isolates and resistance of non-albicans was found in 8% isolates. Conclution: Most common isolates found was C. albicans which show sensitivity to fluconazole, resistance was found in C. krusei isolates.